Bignanoside A "A new neolignan glucoside" and bignanoside B "A new iridoid glucoside" from Bignonia binata leaves. (February 2020) - Mahmoud, Basma Khalaf; Samy, Mamdouh Nabil; Hamed, Ashraf Nageeb Elsayed; Abdelmohsen, Usama Ramadan; Hajjar, Dina; Yamano, Yoshi; Sugimoto, Sachiko; Matsunami, Katsuyoshi; Kamel, Mohamed Salah
Graphical abstract: Highlights: A new neolignan (1 ) and a new iridoid (2 ) were isolated from Bignonia binata leaves. Compound 2, 3, 6 and 10 had DPPH radical scavenging activity. Compounds 4 exhibited cytotoxic activity against A549 cell line. Compounds 4 and 9 showed activity against Trypanosoma brucei brucei S42. Abstract: One new neolignan glucoside; bignanoside A (1 ) and one new iridoid glucoside; bignanoside B (2 ), and one new lignan rhamnoside; (-)-1yoniresinol 3 α - O - α -L-rhamnopyranoside (3 ) reported for the first time, alongside with seven known compounds were isolated from Bignonia binata leaves. The structures of the isolated compounds were elucidated by various spectroscopic methods, including 1D and 2D NMR experiments, as well as HR-ESI-MS. Compound 2 had a potent DPPH radical scavenging activity with IC50 value of 18.34 ± 0.81 μ M. Likewise, compounds 4 and 9 exhibited antitrypanosomal activity with IC50 value of 29.12 ± 1.21 and 17.80 ± 0.32 μ M, respectively, against Trypanosoma brucei brucei S427.